The Denotative and Connotative Meaning in Sheila on 7 Song Lyrics â€œFilm Favoritâ€ - Fadly Fauzan (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
Song Lyrics is a person's expression about something that has been seen, heard or experienced. In expressing their experiences, the poet or composer of the song makes words and language games to create attraction and distinctiveness to the lyrics or poetry. This study aims to see the connotation, denotation, and mythology meaning contained in the object of research, namely the song â€˜Film Favorit' from Sheila On 7. In this study the main theory used is the Roland Barthes semiotic theory. The method used in this study is a qualitative method with a descriptive interpretive approach. The results showed that the lyrics of the song under study contained connotation and denotation meaning in it. Likewise with the myth. This song carries the common myth of love. The myth that contains the value of love illustrates that love must be fought for and makes a commitment to make love secured. Contains about the main character's outpouring of his partner to his partner and how to express his feelings to those he loves. The author's choice of the word